Analysis of Student Errors in Solving Mathematical Literacy Problems Based on the Components of the Mathematical Literacy Process (Department of Mathematics, Universitas Negeri Semarang, 2022)
The low PISA Mathematics score of Indonesia was a strong background in this study. The results of the 2018 Mathematics PISA Indonesia scored 371, lower than the 2015 score of 386. This study is a qualitative study that aims to describe student errors in solving mathematical literacy problems on linear program material. The methods used documentation in the form of answer sheets, observations, and interviews. The validity of the data was obtained by using triangulation techniques from the three methods used. The research sample was taken by 25 students of class X SMA Negeri 4 Purworejo. The results of the research include: (1) as many as 20 students, or 80% of students, have not been able to formulate problems mathematically. Students have not been able to make an example of the problem correctly. (2) as many as 23 students, or 92% of students, have not been able to use mathematical concepts and, have not been able to write mathematical symbols (facts) correctly, have not been able to solve problems with correct mathematical principles and procedures. (3) as many as 22 students, or 88% of students, have not been able to make conclusions and evaluate the problems given. From these results, it can be said that 80% or more of students have not been able to solve math problems from the lowest stages of the literacy process.